The Wellborn Science : Eugenics in Germany, France, Brazil, and Russia. - Adams, Mark B. (Monographs on the history and philosophy of biology., 1990)
The four contributors to this volume examine the eugenic movements in Germany, France, Brazil, and the Soviet Union. The scientific components of those programmes are considered alongside the social, religious, and political forces which have altered their original scientific goals.